Colonoscopic Findings in Patients with Lower Gastrointestinal Bleeding-A prospective Clinical Study - Ali Hassan Mahmood1; Hussein Hama Ali Kakamand; Mohammed Hussen Kadhem (Academic Journal of Clinicians, 2022)
Background: Lower gastrointestinal bleeding which means bleeding from site distal to ligament of Treitz, the colonoscopy both diagnostic and therapeutic purpose in patient with lower GIT bleeding. Objective: to assess the causes of lower GIT bleeding among group of Iraqi patients. Patients and methods: A prospective study done on (141) patients who presented to KCGH with rectal bleeding during the period from first of June to 31st of December 2008, all the patients were examined by video-colonoscopy. Biopsies taken from suspicious lesion. The final diagnosis based on colonoscopy and histopathological finding. Results: Among the 141 patients age range (1-82) years, mean (40.01) years, the most common Colonoscopic finding; colorectal polyp (19.8%), hemorrhoid (17.7%), Colorectal cancer (9.9%), Ulcerative colitis (9.2%), Typhoid Ileo-caecal ulcer (9.2%), infrequent findings are ; diverticular disease (1.4%), crohns disease (1.4%). Colonoscopic intervention was done in 14 patients (9.9%); either by polypectomy or argon plasma coagulation. Conclusion: The Colonoscopy has both diagnostic and therapeutic benefits in lower GIT bleeding yield in lower GIT bleeding, there is a high regional variations in the causes of lower GIT bleeding all over the world.